Effects of hot-cold oil treatment on biological resistance and physical properties of brutia pine sapwood - Ali Var, Ahmet; Yalçin, Mesut; Ümit Yalçin, Ömer; Demir, Mehmet (Maderas. Ciencia y Tecnología, 2021)
This study investigated the physical properties of hot-cold oil-treated Brutia pine sapwood (Pinus brutia) and its biological resistance against wood-decay fungi. Weight percent gain, density, water absorption, and volumetric shrinking were chosen as the physical properties of the wood. White rot (Trametes versicolor) and brown rot (Neolentinus lepideus) were selected as the wood-decay fungi. Two different temperatures and two different time intervals were determined for the hot-cold oil treatment. Castor oil (Ricinus communis), flaxseed oil (Oleum linii), and a mixture of the two were used as the treatment oils (the medium of the hot-cold treatment). The results showed that the physical properties of the hot-cold oil-treated samples improved significantly compared to those of the control samples. In addition, after exposure to the decay fungi, the mass loss of the hot-cold flaxseed oil-treated samples decreased significantly more than in either the untreated samples or those treated with the other oils. There was a significant increase in the water repellent effectiveness and dimensional stability of the Brutia pine sapwood with all hot-cold oil treatments, but the hot-cold castor oil treatment appeared to have had no effect on decay resistance. A hot-cold oil treatment using flaxseed oil or a mixture including it could be a suitable method for improvement of the water repellent effectiveness, dimensional stability, and decay resistance of Brutia pine sapwood, as they both reduced the water uptake and the mass loss against the wood-decay fungi compared to the results of the control samples.